First Encounters in Psychotherapy: Relationship-Building and the Pursuit of Institutional Goals - Scarvaglieri, Claudio (Frontiers in Psychology, 2020)
This article examines how therapists and patients start building and managing relationships and they pursue institutional goals at the same time. Based on a corpus of 70 audio-recorded sessions from client-centered and psychodynamic therapies, I investigate first encounters between therapists and patients as the starting points of any therapeutical process and the place where a relationship between the interactants is established for the first time. Following a microlinguistic qualitative approach and applying methods from conversation analysis and discourse analysis, I show how therapists, on the one hand, try to align with patients to build a positive working alliance and, on the other hand, work to fulfill specific interactive tasks of therapeutic discourse which demand disaligning with the patients’ communicative activity and their interactive expectations. Specific interactive “jobs” that need to be fulfilled in psychotherapy are identified, namely the performance of institutional roles by the interactants, the establishment of an interaction structure and the pursuit of helpful change in the patient. I show at which places in the interaction therapists (dis-)align with the patients’ projected communicative activity and how aligning and disaligning are related to the interactive process and the establishment and performance of these interactive jobs. The analysis shows that, at the beginning of therapy, alignment and disalignment are both important processes for the following reasons: Aligning with the patient contributes to a positive relationship, which has been shown to be vital for successful psychotherapy, while disaligning introduces the patient to the specific discursive mechanisms that characterize therapeutic discourse and constitute the basis for its effectiveness. Overall, the paper argues that reducing therapy to a dichotomy between relationship and “technique” seems overly simplistic, as both aspects need to be handled and managed at the same time.